Three‐dimensional and 3‐Tesla MRI morphometry of knee meniscus in normal and pathologic state. Issue 1 (23rd September 2020) - Kayfan, Samar; Hlis, Rocco; Pezeshk, Parham; Shah, Jay; Poh, Feng; McCrum, Christopher; Chhabra, Avneesh
Abstract: Introduction: To conduct a morphometric analysis of intact and torn menisci using isotropic meniscus plane three‐dimensional (3D) reconstructions on 3‐Tesla MRI and compare 2D versus 3D MRI for meniscus tear characterization. Materials and methods: One hundred thirty three normal menisci from 92 patients (39 male, 53 female), and 38 arthroscopy‐proven torn menisci from 36 patients (23 male, 13 female) were evaluated using 3D isotropic multi‐planar MRI reconstructions and 2D MRI. Two observers measured the tibial plateau height and area, meniscal height, axial plane cross‐sectional areas, and extrusion of intact menisci. Two observers also measured the meniscal tear length, tear area, and residual area of pathological menisci on 2D and 3D MRI. Intraclass correlation coefficients (ICC) were obtained. Institutional Review Board approval was obtained, and the informed consent was waived. Results: Medial meniscus (MM) and lateral meniscus (LM) areas were 503.6 ± 85.1 mm 2 and 396.6 ± 72.0 mm 2 for Observer 1, and 515.8 ± 82.1 mm 2 and 408.0 ± 68.3 mm 2 for Observer 2 (ICC:0.86, 0.87). In torn menisci, average tear length, area, and residual area were 36.3 ± 13.6 mm, 182.6 ± 139.3 mm 2, and 235.4 ± 140.3 mm 2, respectively for Observer 1, and 38.9 ± 14.7 mm, 181.2 ± 135.6 mm 2, 238.2 ± 140.5 mm 2 for Observer 2. In the MM and LM, bucket‐handle and complex tears were largest in areas, respectively. ICCs were excellent (0.91–1.0) on 3D MRI and moderate‐good (0.57–0.81) on 2D MRI. Conclusion: Meniscus morphometry on 3D MRI shows moderate to excellent inter‐observer reliability and meniscus tear extent is more reliably defined on 3D MRI than 2D MRI. Residual meniscus‐area calculation can be performed on 3D MRI.